The Effect of the Variable Frequency Drive of the CNC Roll Grinding Machine on the Operation of Other Devices in Low-Voltage Electrical Installation - Simić, Ninoslav P; Mrvić, Jovan (Proceedings, Electrical engineering institute "Nikola Tesla", 2016)
This paper presents one of the observations that have been collected during the years of testing of electrical installations. A typical case from industrial plant in which are installed loads with variable frequency regulation is analyzed. We propose a simple way by measuring the frequency of the voltage in the objects, to establish the existence of possible irregularities in the operation of the individual units and analyze the influence of the current and voltage signal shape of one load to the work of other loads in the plant. The need for verification of electrical installations immediately upon receipt and installation of electrical equipment is emphasized and the use of the latest standards in the design and selection of equipment, in order to avoid unplanned expenses is recommended.